Artificial mineral films similar to biogenic calcareous shells: oriented calcite nanorods on a self-standing polymer sheet. Issue 12 (15th February 2018) - Nagai, Yuta; Oaki, Yuya; Imai, Hiroaki
Abstract : Micrometre-thick calcareous shells consisting of c -axis-oriented calcite nanorods are produced on an organic sheet as mimetics of foraminiferal tests and isopod cornea cuticles. Abstract : Micrometre-thick calcareous shells consisting of c -axis-oriented calcite nanorods are produced on an organic sheet as foraminiferal tests and isopod cornea cuticles. Here, we produced mineral films similar to biogenic calcareous shells on a self-standing polymer sheet in a supersaturated solution system by multistep crystal growth with the adjustment of the concentration ratio of poly(acrylic acid) (PAA) as a soluble controlling agent. In the initial stage, selective high-density nucleation was achieved at a relatively low PAA to calcium ion ratio ( R = 1.0–1.2) to form of a calcite seed layer on the surface of conventional polyvinyl alcohol. Calcite nanorods elongated in the c direction were then grown perpendicularly to the seed layer in the progressive stages at a relatively high PAA ratio ( R = 1.5–2.0). The artificial mineral films consisting of c -axis-oriented nanorods are suggested to exhibit mechanical properties similar to those of biogenic calcareous shells.